2020
DOI: 10.1111/odi.13637
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical force inhibited hPDLSCs proliferation with the downregulation of MIR31HG via DNA methylation

Abstract: Malocclusion, caries, and periodontitis are considered as three principal oral diseases by the World Health Organization (WHO), and the prevalence of malocclusion is relatively high (Bronkhorst, Truin, Batchelor, & Sheiham, 1991). Malocclusion can affect dental health and function, even influence quality of life in some cases. Orthodontic treatment can successfully correct malocclusion via

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 44 publications
0
13
0
Order By: Relevance
“…Table 3 presents 18 studies that investigated the role of lncRNAs in regulating cellular processes in PDL cells in the presence or absence of stimuli, including studies that compared H-PDL and P-PDL cells [ 60 , 61 , 62 , 63 , 64 , 65 ]. These studies also explored the role of lncRNAs in lipopolysaccharide (LPS)-induced inflammation [ 66 , 67 , 68 , 69 , 70 , 71 ], tumor necrosis factor-alpha (TNF-α)-induced inflammation [ 72 ], mechanical stress [ 73 , 74 , 75 ], hypoxia [ 76 ], and oxidative stress [ 77 ]. To review the outcomes of lncRNA involvement, cell proliferation, apoptosis, inflammatory responses, autophagy, migration, and root resorption were examined.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Table 3 presents 18 studies that investigated the role of lncRNAs in regulating cellular processes in PDL cells in the presence or absence of stimuli, including studies that compared H-PDL and P-PDL cells [ 60 , 61 , 62 , 63 , 64 , 65 ]. These studies also explored the role of lncRNAs in lipopolysaccharide (LPS)-induced inflammation [ 66 , 67 , 68 , 69 , 70 , 71 ], tumor necrosis factor-alpha (TNF-α)-induced inflammation [ 72 ], mechanical stress [ 73 , 74 , 75 ], hypoxia [ 76 ], and oxidative stress [ 77 ]. To review the outcomes of lncRNA involvement, cell proliferation, apoptosis, inflammatory responses, autophagy, migration, and root resorption were examined.…”
Section: Resultsmentioning
confidence: 99%
“…Inflammation-stimulating factors released by bacteria, such as LPS and TNF-α, activate the immune response in PDL cells, thereby aggravating the destruction of alveolar bone. Among the 18 studies that investigated the regulatory role of lncRNAs in PDL cells in response to inflammation and other stimuli, 6 studies compared the inflammatory responses of H-PDL and P-PDL cells [ 66 , 67 , 68 , 69 , 70 , 71 ], 7 studies stimulated PDL cells with LPS or/and TNF-α to mimic periodontal inflammation [ 66 , 68 , 69 , 70 , 71 , 72 , 74 ], 3 studies stimulated PDL cells with mechanical stress [ 73 , 74 , 75 ], 1 study subjected PDL cells to hypoxia [ 76 ], and 1 study subjected cells to oxidative stress [ 77 ]. Under these stimuli, the biological activities of PDL cells, including cell proliferation, apoptosis, inflammatory responses, osteogenic differentiation, and autophagy, were explored.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…26 Another study employing the same force type and magnitude for PDLCs reported that static compressive force reduced cell proliferation and the Ki67-positive cell population. 27 This phenomenon occurred via regulation of MIR31HG . 27 …”
Section: Discussionmentioning
confidence: 99%
“…The cell fractionation assays were performed using a Nuclei Isolation Kit (Invent Biotechnologies, Beijing, China) to separate cytoplasmic and nuclear RNA as previously described [ 20 ]. Briefly, cytoplasm extraction buffer was added to the harvested cells with vigorous vortexing for 15 s. After incubation on ice for 5 min, the mixtures were centrifuged at top speed in a microcentrifuge at 4 °C for 5 min.…”
Section: Methodsmentioning
confidence: 99%